Flexible and stretchable electrode based on multiwalled carbon nanotube/deproteinized natural rubber composites. Issue 12 (3rd February 2017) - Tangkitthanachoke, Paweenuch; Petcharoen, Karat; Paradee, Nophawan; Sangwan, Watchara; Sirivat, Anuvat
Abstract : One of stretchable electronic devices is known as the compliant electrode which can retain good electrical conductivity under deformation. Compliant electrodes from MWCNTs and DPNR were prepared by using a UV‐curing process and Triton X‐100 as a dispersing agent. The effect of Triton X‐100/MWCNTs volume ratio was investigated by transmission electron microscopy indicating the highest dispersion was obtained at the volume ratio of 15.6. The mechanical and electrical properties were investigated by a melt rheometer in a tension mode. The 3%v/v MWCNTs composite possessed an excellent mechanical behavior (Young's modulus = 1.27 × 10 6 Pa) and a high electrical conductivity (1.03 S/cm) relative to previous works. Under the same experimental conditions, a commercial compliant electrode named Danfoss exhibited the Young's modulus and electrical conducivity values of 7.56 × 10 6 Pa and 2.54 × 10 −2 S/cm, respectively, which were inferior to the 3%v/v MWCNTs/DPNR. Moreover, the composite film still retained good electrical behaviors under 100% strain, high extentional strain rate of 1 s −1, high flexed angle, and repeated stretching cycles (40% strain, 50 times) due to the intimate compatibility between the MWCNTs and the elastomer matrix. POLYM. ENG. SCI., 57:1356–1366, 2017. © 2017 Society of Plastics Engineers